Marketingová strategie vybrané mezinárodní společnosti - Sklenářová, Petra (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Diplomová práce se zabývá marketingovou strategií mezinárodní společnosti. V teoretické části je uvedena charakteristika marketingu a jednotlivých vybraných analýz. Praktická část analyzuje mezinárodní společnost WABCO Holding Inc. a obsahuje analýzy makroprostředí a mikroprostředí a průzkum. Na závěr jsou představeny návrhy sestavené pomocí zjištěných dat z analýz a průzkumu, které představují opatření na zlepšení marketingové strategie společnosti.

The diploma thesis deals with the marketing strategy of an international company. The theoretical part presents the characteristics of marketing and selected analyzes. The practical part analyzes the international company WABCO Holding Inc. and includes macro-environment and micro-environment analyzes and research. Finally, proposals compiled using the data obtained from analyzes and research are presented, representing measures to improve the company's marketing strategy.
Marketing Strategy of the Selected International Company
Keywords: Mezinárodní společnost; marketingová strategie; marketingová komunikace; SWOT analýza; průzkum spokojenosti; International company; marketing strategy; marketing communication; SWOT analysis; satisfaction research